Triagem neonatal para infecção da doença de chagas congênita : avaliação da prevalência ao nascer na região sul de Sergipe - Santos, Fábia Regina dos (2018)
Introduction: Chagas Disease (CD) is one of the main causes of morbimortality in the Americas, with an estimated prevalence of six to seven million people infected worldwide. In Brazil, improvement of vector control and blood banks, the congenital transmission of the CD has been receiving an important epidemiologic role. It is known that most children infected by congenital route is asymptomatic and the treatment presents high efficiency and safety for them, there is an urgency for early diagnose and treatment. The neonatal screening, also known as teste do pezinho, is considered a good strategy for the identification of vertical transmission in public health. The present knowledge of Congenital Chagas Disease (CCD) epidemiology in Sergipe state is still limited. Considering the epidemiologic importance of CD in Sergipe, specially in the south area, and the scarcity in data for this field, the present research was designed to attend these specific needs. Goal: Estimate the prevalence of CCD among the neonatal from the south area of Sergipe state, by means of the National Neonatal Screening Program (PNTN) study. Methodology: This is a transversal study. The study material was composed of 3952 blood samples, in filter paper, of neonatal screened by the National Program of Neonatal Screening of Sergipe (PNTN/SE) from the period between July 2015 to July 2016. From these samples, 203 were considered inadequate and 3749 were submitted to ELISA IgG test, which diagnosed the presence of two positive samples. 20% of those with negative results were submitted to the Quantitative Indirect Immunofluorescence test which, in number, was 750 samples, were Immunofluorescence was considered the second test. A pregnant woman presented positive for CD in the confirmatory tests, but the son presented negative for the disease. The data were analyzed by means of Epi Info 7.1.4 software. Results: No newborns with congenital Chagas' disease were identified in the Southern Region. A puerperal patient with the disease was found, whose prevalence was 0.02%. Conclusion: No CCD was found among the newborns in the South of Sergipe. However, the CD infection was found in woman of reproductive age alerting for the need of detection and early treatments as a public health policy for the prevention and disease control. The CD detection by means of the PNTN was an efficient strategy, which can be sustained by the Sistema Único de Saúde (SUS) and included in the pre-natal exams and tracking of newborns in the disease endemic areas.